Hair casts or pseudonits. A rare hair disorder. - Sotiriou, E.; Chatzigeorgiou, M.; Apalla, Z.; Panagiotidou, D. (European Journal of Pediatric Dermatology, 2009)
Hair casts are a relatively rare condition of the scalp hair characterized by the presence of grayish-white formations, encircling the hair shafts and sliding freely upon them. We report a case of hair casts arising in a 9-year-old girl, who frequently styled her hair in ponytail. Lesions were initially misdiagnosed as nits and the patient had been repeatedly treated during the last 2 years for pediculosis capitis.